The Influence of Time Management on Learning Outcomes of Students of Pre-service Teachers in Lubuklinggau - Edy Susanto; Meilida Eka Sari (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: The Influence of Time Management on Learning Outcomes of Students of Pre-service Teachers in LubuklinggauThis study aims to describe the effect of time management on student learning outcomes of Early Childhood Islamic Education in Mathematics and Science Courses at the Al-Azhar Institute Lubuklinggau, South Sumatra Province. The method in this research is a quantitative approach. The sample in this study were third semester students of Early Childhood Islamic Education Study Program, totaling 31 respondents. Data collection instruments: time management questionnaires using Google forms and learning outcomes using test sheets. The data analysis technique uses simple regression by utilizing the SPSS version 20 application. The results of this study show that the results of the simple linear regression analysis test show that the Sig value is 0.000 <0.05, so H0 is rejected. This is also in accordance with the test results of the coefficient of determination showing that R Square is 0.542. Thus, the effect of time management on learning outcomes is 54.2%. So it can be concluded that there is a positive and significant effect of time management on learning outcomesAbstrak: Pengaruh Manajemen Waktu Terhadap Hasil Belajar Anak Usia Dini Siswa PAI Al-Azhaar IPA LubuklinggauPenelitian ini bertujuan untuk mendeskripsikan pengaruh manajemen waktu terhadap hasil belajar mahasiswa Pendidikan Islam Anak Usia Dini Mata Kuliah Matematika dan Sains Di Institut Al-Azhar Lubuklinggau Propinsi Sumatera Selatan. Metode dalam penelitian ini adalah pendekatan kuantitatif. Sampel dalam penelitian ini adalah mahasiswa semester tiga prodi Pendidikan Islam Anak Usia Dini yang berjumlah 31 orang responden. Instrumen pengumpulan data: angket manajemen waktu menggunakan google form dan hasil beajar menggunakan lembar tes. Teknik analisis data menggunakan regresi sederhana dengan memanfaatkan aplikasi SPSS versi 20. Hasil penelitian ini menunjukkan dari hasil uji analisis regresi linear sederhana menunjukkan bahwa nilai Sig 0.000 <0.05 maka H0 ditolak. Hal ini juga sesuai dengan hasil uji koefisien determinasi menunjukkan bahwa R Square 0.542. Dengan demikian pengaruh antara manajemen waktu terhadap hasil belajar sebesar 54.2%. jadi dapat disimpulkan bahwa terdapat pengaruh positif dan signifikan antara manajemen waktu terhadap terhadap hasil belajar